Crossing the Borderline of “Null Policy”: the U.S. Federal Congress as a Language Policy-Making Entity - Czeglédi, Sándor (FOCUS: Papers in English Literary and Cultural Studies, 2024)
It is impossible for a state to be neutral toward language. Governments necessarily make choices about which language or languages they will communicate in. The idea of “linguistic disestablishment” (Kymlicka and Patten 32) is an illusion, since even a hypothetical “null policy” (Wiley 49) with respect to minority languages inevitably favors the majority (usually official) language and its speakers (Fishman, “From theory to practice” 454). Linguistic non-intervention - an alleged laissez-faire language policy by the state—will result in “linguistic Social Darwinism” (Kontra 109), which is clearly detrimental to minority interests. As Shirley Brice Fleath pointed out three decades ago, the absence of explicit policy is in itself an act of language policy (qtd. in Paulston 475).